Studi Fiqih Hubungan antara Fiqih dan Hukum Positif di Indonesia - AZ-ZAHRA, MAULANY (Maliki Interdisciplinary Journal, 2025)
The relationship between fiqh and positive law in Indonesia is a crucial aspect of understanding the evolution of the national legal system, especially in the modern era. Fiqh, as part of Islamic law, is dynamic and develops according to context through the ijtihad of scholars, with primary sources from the Qur’an, Hadith, ijma’ (consensus), and qiyas (analogical reasoning). Meanwhile, positive law in Indonesia is formulated based on the constitution, legislation, and decisions of state institutions that hold formal binding authority. This article explores the comparison of concepts, sources of law, authority, and scope of both legal systems. Additionally, it discusses the influence of fiqh on positive law in Indonesia, which is reflected in regulations such as the Compilation of Islamic Law (KHI), the Marriage Law, and zakat regulations. Case studies, such as child marriage and inheritance laws, illustrate the challenges in harmonizing these two legal systems. On one hand, fiqh plays a role in shaping legal norms based on religious values; on the other hand, positive law must adapt to broader principles of j~ustice and human rights. This highlights the significant role of fiqh in societal life. In conclusion, despite fundamental differences, fiqh remains an integral part of the formation of positive law in Indonesia, particularly in social and religious aspects. Therefore, a contextual approach is needed to create a fa~ir and relevant legal balance that meets the needs of society.